2018
DOI: 10.1111/php.12885
|View full text |Cite
|
Sign up to set email alerts
|

The Solar Ultraviolet Environment at the Ocean

Abstract: Atmospheric and oceanic radiative transfer models were used to compute spectral radiances between 285 and 400 nm onto horizontal and vertical plane surfaces over water. The calculations kept track of the contributions by the sun's direct beam, by diffuse-sky radiance, by radiance reflected from the sea surface and by water-leaving radiance. Clear, hazy and cloudy sky conditions were simulated for a range of solar zenith angles, wind speeds and atmospheric ozone concentrations. The radiances were used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…230 The solar UV radiation environment relevant to recreational boaters on oceans was simulated with radiative transfer models that take scattering and absorption process in the atmosphere and the ocean into account. 231 231,232 also suggest that swimming in the ocean provides little protection from sun exposure. Even for depths as large as one meter below the surface, the UVI can be comparable with that at the surface.…”
Section: Personal Exposurementioning
confidence: 99%
“…230 The solar UV radiation environment relevant to recreational boaters on oceans was simulated with radiative transfer models that take scattering and absorption process in the atmosphere and the ocean into account. 231 231,232 also suggest that swimming in the ocean provides little protection from sun exposure. Even for depths as large as one meter below the surface, the UVI can be comparable with that at the surface.…”
Section: Personal Exposurementioning
confidence: 99%
“…Irrespective of the height of the sun in the sky and the direction a subject is facing with respect to the sun, the contribution of UV radiation resulting from surface reflectance and emerging from the sea (backscattered), is never more than equivalent to a UVI of 0.7 [22]. For a sunbather, who is lying supine on a beach or the deck of a boat, there is no contribution from UV radiation reflected from the ocean to their erythemal exposure.…”
Section: Outdoor Leisure Pursuitsmentioning
confidence: 99%
“…In data reported elsewhere, we showed that wind speed, which impacts on the choppiness of the sea surface, makes virtually no difference to the contribution of the total reflected radiation to erythemal exposure on a vertical surface for a given solar zenith and orientation with respect to the sun.…”
Section: Resultsmentioning
confidence: 58%
“…The reflectance of incident solar UV radiation (wavelength range: 285‐400 nm) for a range of solar altitudes was calculated using the HydroLight radiative transfer numerical model, which computes radiance distributions and related quantities such as irradiance and reflectance in any water body; details are given elsewhere …”
Section: Methodsmentioning
confidence: 99%